Virus Factories - Fernández de Castro, Isabel (Encyclopedia of Virology, 2021)
Viral factories are intracellular compartments of the host cell that contain viral replication organelles and necessary elements for assembly and maturation of new infectious viral particles. In this article we revise the methods used to study viral factories and the current knowledge on the structure, functions and biogenesis of these structures. We also describe some of the most emblematic examples of viral factories characterized so far. Finally, we describe how the identification of mechanisms involved in the biogenesis and functional architecture of viral factories will provide new means for antiviral intervention.